Establishing an Agenda for Biomedical Informatics - Maojo, V.; Martin-Sanchez, F.; Billhardt, H.; Iakovidis, I.; Kulikowski, C. (Methods of Information in Medicine, 2003)
Objective: To describe potential areas of collaboration between Medical Informatics (BI) and Bioinformatics (BI) and their effects on planning future work in both disciplines.Methods: Some reflections on the objectives and rationale underpinning MI and BI are given, and preliminary results from the BIOINFOMED workgroup, supported by the European Commission, are introduced. Results: Applications from both subfields suggest topics for sharing and exchange between the subfields within the emerging field of Biomedical Informatics. Conclusions: We suggest how the nature and degree of collaboration between the sub-disciplines can impact future work in molecular medicine.
Keywords: Medical informatics; bioinformatics; synergy; BIOINFOMED study